2021
DOI: 10.1007/s12598-020-01698-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale architectures boosting thermoelectric performance of copper sulfide compound

Abstract: Owing to their high performance and earth abundance, copper sulfides (Cu 2− x S) have attracted wide attention as a promising medium-temperature thermoelectric material. Nanostructure and grain-boundary engineering are explored to tune the electrical transport and phonon scattering of Cu 2− x S based on the liquid-like copper ion. Here multiscale architecture-engineered Cu 2− x S are fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…30,31 The Cu LMM Auger spectrum in Figure S7 further proves the existence of Cu 1+ . 32 According to the peak areas, the relative ratios of Cu 1+ /Cu 2+ are estimated to be 1.4:1 for SNC@Cu 2 S and 1.08:1 for SNC@Cu 1.96 S. The ratio of Cu 1+ /Cu 2+ decreases from 1.4 to 1.08, confirming the formation of Cu vacancies in SNC@ Cu 1.96 S 29,33 inferred from the HR-TEM, XRD, and EPR results. The S 2p XPS spectra of SNC@Cu 1.96 S and SNC@ Cu 2 S are shown in Figure S8.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…30,31 The Cu LMM Auger spectrum in Figure S7 further proves the existence of Cu 1+ . 32 According to the peak areas, the relative ratios of Cu 1+ /Cu 2+ are estimated to be 1.4:1 for SNC@Cu 2 S and 1.08:1 for SNC@Cu 1.96 S. The ratio of Cu 1+ /Cu 2+ decreases from 1.4 to 1.08, confirming the formation of Cu vacancies in SNC@ Cu 1.96 S 29,33 inferred from the HR-TEM, XRD, and EPR results. The S 2p XPS spectra of SNC@Cu 1.96 S and SNC@ Cu 2 S are shown in Figure S8.…”
Section: Resultsmentioning
confidence: 63%
“…For the Cu 2p spectrum of SNC@Cu 1.96 S in Figure g, the deconvoluted peaks centered at 954.1 eV (Cu 2p1/2) and 934.05 eV (Cu 2p3/2) are assigned to Cu 2+ , and the peaks at 952.25 eV (Cu 2p1/2) and 932.27 eV (Cu 2p3/2) are assigned to Cu 1+ or Cu 0 . , The Cu LMM Auger spectrum in Figure S7 further proves the existence of Cu 1+ . According to the peak areas, the relative ratios of Cu 1+ /Cu 2+ are estimated to be 1.4:1 for SNC@Cu 2 S and 1.08:1 for SNC@Cu 1.96 S. The ratio of Cu 1+ /Cu 2+ decreases from 1.4 to 1.08, confirming the formation of Cu vacancies in SNC@Cu 1.96 S , inferred from the HR-TEM, XRD, and EPR results. The S 2p XPS spectra of SNC@Cu 1.96 S and SNC@Cu 2 S are shown in Figure S8.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have proposed that the atoms in superionic conductors can migrate freely within the framework. The above-mentioned theory has been fully validated in the Cu 2 Se, Cu 2 S, and Ag 9 GaSe 6 systems . Zhao et al confirmed that the zT value of superionic conductors could be optimized by introducing lattice vibration behaviors, , configuration entropy effects, doping effects, and hierarchical structures .…”
Section: Introductionmentioning
confidence: 95%
“…Even so, PBN has mostly existed in a powder state, thus making it difficult to separate from wastewater aer adsorption. [19][20][21][22] Poor recyclability has limited its practical application in the eld of water treatment. The combination of PBN with magnetic nanomaterials to prepare composite adsorbents is an effective strategy to solve this problem.…”
Section: Introductionmentioning
confidence: 99%